Development of Learning Media through Interactive Quiz - Machnunah Ani Zulfah; Akhmad Mahmudi (SCHOOLAR: Social and Literature Study in Education, 2021)
Pandemic covid-19 requires all sectors to make various changes and innovations, especially in the education sector which must maintain the implementation of the learning process well and run smoothly. Therefore, all education sectors are required to make changes to the learning process that was originally conducted directly between students and teachers changed into an online learning process. Thus, teachers and students must be ready to adapt to new breakthroughs and challenges in the learning system applied in the elementary school. quizizz is an application used to create interactive online-based quizzes that can be played on computers and mobile phones. In this study using research and development model (R&D) consisting of the following steps: solving potentials and problems, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, product revisions, mass production. Where in the purpose of this research is to develop and explain the utilization of learning media application quizizz based on mobile learning. on the test validator experts resulted in that the product is said to be valid and feasible because it gets 93% and in the initial product test phase produces an A score of 4 people (67%), and at the stage ofthe comprehension test with 30 students after memberi response to 15 statements point to the choice of answers 93% students answer yes. And students who voted didn'tmake as much as 11%.